2021
DOI: 10.1002/hep4.1835
|View full text |Cite
|
Sign up to set email alerts
|

Traf2 and NCK Interacting Kinase Is a Critical Regulator of Procollagen I Trafficking and Hepatic Fibrogenesis in Mice

Abstract: Hepatic fibrosis is driven by deposition of matrix proteins following liver injury. Hepatic stellate cells (HSCs) drive fibrogenesis, producing matrix proteins, including procollagen I, which matures into collagen I following secretion. Disrupting intracellular procollagen processing and trafficking causes endoplasmic reticulum stress and stress-induced HSC apoptosis and thus is an attractive antifibrotic strategy. We designed an immunofluorescence-based small interfering RNA (siRNA) screen to identify procoll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Collagen I, which plays a vital role in the formation of bone, skin, and tendon formation, relies on efficient secretion facilitated by the ER-to-Golgi transport of procollagen I. Research has demonstrated that the deletion or depletion of TNIK disrupts the secretion of procollagen I without affecting intracellular procollagen I protein levels ( 48 ). This disruption suggests that TNIK may be involved in viral entry and replication, particularly since some viruses exploit host secretory pathways, including the ER-to-Golgi transport.…”
Section: Discussionmentioning
confidence: 99%
“…Collagen I, which plays a vital role in the formation of bone, skin, and tendon formation, relies on efficient secretion facilitated by the ER-to-Golgi transport of procollagen I. Research has demonstrated that the deletion or depletion of TNIK disrupts the secretion of procollagen I without affecting intracellular procollagen I protein levels ( 48 ). This disruption suggests that TNIK may be involved in viral entry and replication, particularly since some viruses exploit host secretory pathways, including the ER-to-Golgi transport.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NCB-0846 can disrupt the transport and secretion of type I procollagen and inhibit the production of matrix proteins to regulate liver fibrosis. 39 In PCa, matrix proteins can induce tumor cell metastasis and adhesion to bone cells. 39 Although previous studies have demonstrated that NCB-0846 has a good therapeutic effect in ERG-positive PCa, whether it has the effect of regulating PCa EMT and bone metastasis has not been verified.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that MMP9 [133], S100A12 [148], HP (haptoglobin) [149], OSM (oncostatin M) [150], PRDM5 [151], TSPO (translocator protein) [152], IL18RAP [153], ADAMDEC1 [154], IL1RN [155], SCN9A [156], FADS2 [157], NCF4 [158], SERPINB1 [159], TNFRSF13B [160], IL2RB [161], DLG5 [162], FASLG (Fas ligand) [163], GPR68 [164], IL2RA [161], TCF4 [165], TAGAP (T cell activation RhoGTPase activating protein) [166], ABCB1 [167], FCRL3 [168], ITGB7 [169], PTGER4 [170] and TRAF3IP2 [171] are altered expression in gastrointestinal complications. Recent studies reported that MMP9 [133], S100A12 [172], IGF2 [173], GPR84 [174], SOCS3 [175], IGFBP2 [176], HP (haptoglobin) [177], MMP8 [178], OSM (oncostatin M) [179], TLR5 [180], S100A9 [181], PLIN5 [182], NRG1 [183], LCN2 [184], TSPO (translocator protein) [185], PLAU (plasminogen activator, urokinase) [186], PPBP (pro-platelet basic protein) [187], UPP1 [188], ALOX5 [189], IL1RN [190], CYP1B1 [191], DGAT2 [192], MSRA (methionine sulfoxidereductase A) [193], ADAM9 [194], CPEB4 [195], IRS2 [196], FADS2 [197], SLC22A4 [198], PFKFB3 [199], CTSD (cathepsin D) [200], ADAM12 [201], CD80 [202], ERBB2 [203], FASLG (Fas ligand) [204], CNR2 [205], SOCS2 [206], ABCB1 [207], CD74 [208], FCRL3 [209], PARP1 [210], TXNIP (thioredoxin interacting protein) [211], TULP3 [212], HSPA8 [213], TNIK (TRAF2 and NCK interacting kinase) [214], PDCD4 [215…”
Section: Discussionmentioning
confidence: 99%